DO VOLATILITY AND PRICE DECLINE MATTER? EVIDENCE FROM FALLING KNIVES IN INDONESIA USING LOGISTIC REGRESSION - Teresia Angelia Kusumahadi; Synthia Madyakusumawati (Universitas Katolik Indonesia Atma Jaya, 2026)
This research examines the recovery probability of stocks experiencing sharp price declines or falling knives from 2010 to 2020 in Indonesia. Using data from Indonesia Stock Exchanges, this study identified 194 falling knife observations and evaluated whether the stocks could provide positive returns within three years after the price drop.The analysis uses logistic regression with a bootstrapping approach, focusing on price-based determinants, namely, the magnitude of price decline and return volatility. The results indicate that volatility has a negative impact on the probability of stock recovery. The higher the volatility of a stock, the lower the likelihood that it will return to its pre-decline price. In contrast, the magnitude of the price decline is not statistically associated with recover probability. Furthermore, only 22.7% of falling knives consistently yield positive returns over the three-year period. These findings indicate the small number of stocks that recover after a sharp decline. These findings also emphasize the importance of volatility as a key factor in assessing stock recovery probability.